Conceptualization studies of the coaching process - Horino, H. (Science in Olympic Sport, 2020)
As the coaching process includes many elements, in the sports psychological research arena, a wide variety of coaching themes have been explored. Expert coaches utilize their acquired knowledge and practice appropriate decision making and behavior depending on the situation. Accordingly, investigating the coaching style of experienced and successful coaches can provide a model to facilitate the development of less experienced coaches. In this article the "conceptualization studies of the coaching process", were review ed largely dealing with utilizing experienced coaches to create a coaching model. Were discuss ed future challenges in this area and related areas of research. It is essential to integrate various conceptual models with research developments and to utilize this body of knowledge to create a practitioner-oriented model that will be applicable to both coaching practice and athlete development.